Nomenclatural notes in the Pleurothallidinae (Orchidaceae): Phloeophila - Chiron, Guy R. (2016)
Two of us found some years ago that Phloeophila nummularia, type species of the genus Phloeophila, was placed in a molecular phylogentic study in Pabstiella. In this article, we show with the inclusion of new sequences of Phloeophila that this result was not correct. Phloeophila forms a unique clade in Pleurothallidinae and is not closely related to Pabstiella. In addition, the exclusion of three species, one transferred to Dryadella and two others to Acianthera, is proposed.